A Flexible Framework for Natural User Interface in the Metaverse - Rodríguez, Graciela (2024)
The metaverse is conceptualized as an immersive 3D virtual environment that facilitates human social interaction, entertainment, work, and daily living, while simultaneously integrating with the physical world across these domains. Given the extensive variety and frequency of user interactions within the metaverse, optimizing the realtime collection, transmission, processing, and feedback of user data from the physical to the virtual realm becomes increasingly critical. Interaction technologies enable the mapping of user actions to the virtual world, thereby enhancing the interaction experience within the metaverse. However, the vast number of existing devices makes achieving this goal challenging. This paper proposes a framework for the development of metaverse systems, grounded in current immersive technologies. The proposed framework focuses on low-cost hardware and a unified architecture to manage the diverse range of devices available on the market. Three case studies are presented to demonstrate the feasibility of the proposal.